2009
DOI: 10.1523/jneurosci.4650-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Associated Kinase II (ROCKII) Limits Axonal Growth after Trauma within the Adult Mouse Spinal Cord

Abstract: Rho GTPases are thought to mediate the action of several axonal growth inhibitors in the adult brain and spinal cord. RhoA has been targeted pharmacologically in both humans and animals to promote neurite outgrowth and functional recovery following CNS trauma. However, rat spinal cord injury studies suggest a complicated and partial benefit of inhibiting Rho or its downstream effector, Rho-associated kinase (ROCKII). This limited benefit may reflect inhibition of other kinases, poor access, or a minimal role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 63 publications
0
91
0
5
Order By: Relevance
“…Adult dorsal root ganglion neurons were cultured and analyzed for outgrowth in the presence or absence of myelin fractions, as described (30,44).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult dorsal root ganglion neurons were cultured and analyzed for outgrowth in the presence or absence of myelin fractions, as described (30,44).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse thoracic spine level T6 spinal cord injury was achieved in ephrinB3 −/− and ephrinB3 +/+ littermates after dorsal laminectomy (30,37,44,45). Either dorsal hemisection or near-total transection was performed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This proportion was significantly increased to 37% after 14 days of continuous NGF infusion through catheters placed in the dorsal spinal cord (Jones et al, 2001). These regenerating axons penetrate spinal cord white matter and grow up to 3 mm past the dorsal root entry zone (Duffy et al, 2009). Additional experiments confirmed this NGF-driven regrowth of injured sensory fibers into the spinal cord and revealed the regenerating axons as positive for calcitonin gene-related peptide, a marker for small diameter, unmyelinated peptidergic axons (Lykissas et al, 2007).…”
Section: Discussionmentioning
confidence: 74%
“…The ability of CSPGs to affect intracellular signaling has been well documented. Studies have identified the roles of the small GTPase Rho and its downstream effector Rho kinase (ROCK) in CSPG mediated growth cone collapse and inhibition of neurite outgrowth (80)(81)(82). CSPGs induce calcium transients in dissociated DRG neurons growing across a barrier of laminin and CSPGs (83) and activate calcium-dependent protein kinase C (PKC) (84) leading to phosphorylation of epidermal growth factor receptor (EGFR) kinase (85) and increased the activity of both serine/threonine protein kinase Akt and glycogen synthase kinase-3 (GSK-3β) (86).…”
Section: The Discovery Of Cspg Receptors and Their Impact On Regenmentioning
confidence: 99%